Recent advances on ISRU technologies and study of microgravity impact on blood cells for deep space exploration - Cao, Giacomo; Concas, Alessandro; Orrù, Roberto; Licheri, Roberta; Sani, Elisa; Dell’Oro, Aldo; Fais, Giacomo; Manis, Cristina; Manca, Alessia; Uras, Giuseppe; Caboni, Pierluigi; Locci, Antonio Mario; et al. (Frontiers in Space Technologies, 2023)
The long-term solution to problems like overcrowding, fossil fuel depletion, climate change, and decreasing natural resource availability could be overcome through space colonization and human presence in space, as well as the exploitation of extraterrestrial natural resources. In keeping with this, the objective of this work is to analyze current advancements in technology development for deep space exploration and colonization made by our research team as well as by other organizations with which we are collaborating. First, a method for producing tangible goods suited for industrial or civil installations on the Moon, Mars, or asteroids, using in-situ available regolith as the main resource, is discussed. . In this regard, a new process based on the occurrence of self-propagating high-temperature synthesis (SHS) reactions was developed for the fabrication of composite ceramics to be used as construction materials. A theoretical analysis of the process using proper dimensionless numbers is also described to offer potential explanations of the key experimental evidences presented in the relevant literature. For instance, it is found that free convection likely plays a crucial role to make SHS front velocity higher under terrestrial conditions when the reaction ignition is carried out from the bottom side, instead of the top side, of reacting mixture. Next, a method that uses the atmosphere and regolith of Mars as raw feedstock to produce in-situ useful material such as oxygen, water, food, fuels and fertilizers, is considered. In the next section, the potential for cultivating Spirulina platensis to provide nourishment for the Martian crew is examined. The possible use of sintered lunar regolith simulants such as JSC-1A is also considered for potential thermal energy storage and solar energy harvesting applications, within the context of resource exploitation. Sintered regolith simulant exhibited, compared to the native material in powder form, superior solar absorptance, which makes it suitable for sunlight absorbers in architectures with a cavity-like solar receiver. Finally, a new study is reported which combines biochemical and biophysical approaches in order to compare, under simulated microgravity and under terrestrial conditions, the functioning and structure of red blood cells, over various intervals of time.